Intrapartum ultrasound and mother acceptance: A study with informed consent and questionnaire - Antonio Malvasi; Gianluca Raffaello Damiani; DI Naro Edoardo; Amerigo Vitagliano; Miriam Dellino; Reuven Achiron; Kosmas Ioannis; Antonella Vimercati; Maria Gaetani; Ettore Cicinelli; Marina Vinciguerra; Ilaria Ricci; et al. (European Journal of Obstetrics & Gynecology and Reproductive Biology: X, 2023)
Introduction: Intrapartum ultrasound (IU) is used in the delivery ward; even if IU monitors the labouring women, it could be perceived as a discomfort and even as an“ obstetric violence”, because it is a young technique, not often well ''accepted''. A group of clinicians aimed at obtain an informed consent from patients, prior to perform a translabial ultrasound (TU). The aim of this study was to evaluate the acceptance of both translabial and transabdominal IU. Methods: In this study, performed at the University Hospital of Bari (Unit of Obstetrics and Gynecology), were enrolled 103 patients in the first or second stage of labor in singleton cephalic presentation. A statistical frequency and an association analysis were performed. As a significant result, we consider the peace of mind/satisfaction and the” obstetric violence”. IU was performed both transabdominal and translabial to determine the presentation, head positions, angle of progression and head perineum distance. During the first and second stage of labor, the ASIUG questionnaires (Apulia study intrapartum ultrasonography group) were administered. Results: 74 (71, 84%) patients underwent IU and 29 had a vaginal examination (28, 15%). Significant less “violence” has been experienced with a IU (73 out 74/98, 65%) and only one person (1 /1, 35%) recorded that. On the contrary, 10 patients (10/29) perceived that “violence” (34, 48%) while 19 (65, 52%) did not respond on a similar way, after a vaginal examination (VE). More patients felt satisfaction (71 out 74/95, 95%) with the use of IU and only 3 (3/4, 05%) felt unease. A different picture was evident in the vaginal examination group. Only 17 patients (17 out 29/58, 62%) felt comfort while 12 (41, 38%) felt unease. Conclusions: In our study, IU use is well accepted by most of patients, because it could reassure women about their fetal condition. Moreover, they can see the fetus on the screen, while the obstetrician is performing the US and this is important for a visual feedback, in comparison with the classical VE.